Resource Based Learning for Teaching and Learning English in Digital Environments - Muhammad Nazil Iqdami (Register Journal, 2016)
This paper presents a conceptual framework on the implementation of Resource Based Learning (RBL) in English as a Foreign Language (EFL) class. Resource based learning emerges as the proponent of constructivism as well as a response to the rapid development of information and communication technology (ICT) and its influence in education. Digital technologies pose potential opportunities in changing the face of education. The affordances of digital technologies empower more student-centered learning and more accessible educational information. Teaching English for foreign learners is dynamic and requires innovations. Admittedly, most English learners in Indonesia need more exposure to authentic English learning resources, and digital technologies are very potential in accommodating their needs. Resource based learning sets an innovative framework and systematic approach for English educators in designing digital technology-based instructions.